Shia Sunni Dynamics in Palembang City - Yen Fikri Rani; Febriani, Fenti; Syahril Jamil; Muhammad Torik; Muhammad Abdillah (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2025)
This study aims to analyse the dynamics between Shia and Sunni Muslims in Palembang City, which is important considering that these two sects often experience friction in the religious social reality, leading to conflict. The long history of Shia and Sunni has always been an intriguing topic for discussion. Hegemony over other groups is not merely about sectarian doctrinal differences but also impacts all aspects of life, including social, political, economic, educational, and legal dimensions. The study employs a qualitative method with a literature review approach to examine the phenomena occurring between Shia and Sunni groups in Palembang City. The data was then analysed to draw conclusions from the study. The results of this study indicate that the Shia and Sunni groups in Palembang City experience a harmonious dynamic. This is not only evident in the history between Shia and Sunni, but more importantly, this study shows how Shia and Sunni groups build relationships through various approaches. Of course, all of these aspects are inseparable from the important role of ideology believed by both Shia and Sunni groups.